REMEDIASI MISKONSEPSI FLUIDA STATIS SISWA SMAN 5 PONTIANAK MENGGUNAKAN PROCESS ORIENTED GUIDED INQUIRY LEARNING - Jaya, Fitra Cipta; Maria S, Haratua Tiur; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this study was to measure the effect of remediation activity through Process-Oriented Guided Inquiry Learning (POGIL) model on misconception among grade XII student’s at SMAN 5 Pontianak. One group pretest-posttest experimental design was used in this study. The population is all students of class XII SMAN 5 Pontianak. The sample was taken by intact group so that it was obtained class XII IPA 3 which have 32 students. The instrument used a diagnostic test which amounted to 9 multiple-choice questions with open reasons. The percentage of decreasing number of students who had misconceptions after being given a misconception remediation with the POGIL model on static fluid was 44%. McNemar test was carried out with a significance level of 5% indicating that there was a significant change in student’s conception after being given remediation activities using the POGIL model. This model is effective in remediating student’s' misconceptions on static fluid with the effect size of 0.428 in the high category according to the Hattie barometer. So that the POGIL model is effective to reduce the number of misconceptions of students. Keywords: Process Oriented Guided Inquiry Learning, POGIL, Remediation, Misconception, Static Fluid